Analisis Sistem Pelayanan Umrah dalam Meningkatkan Kepuasan Jemaah (Studi Kasus PT. Nur Hamdalah Travel) - Erta Pramita (Program Studi Manajemen Dakwah Fakultas Ushuluddin Dan Dakwah Uin Raden Mas Said Surakarta, 2025)
Umrah service is an important aspect that determines the quality of the worship experience and increases the satisfaction of the congregation. This study aims to analyze the effectiveness of the Umrah service system in an effort to increase the satisfaction of the congregation. This study uses a qualitative approach with descriptive methods. Data collection techniques include observation, interviews, and documentation. The results of the study indicate that Nur Hamdalah Travel's service is considered effective because it is supported by Having professional employees and guides (muthawwif); Adequate facilities and infrastructure support the smooth running of each service process; Responsive service, and alert in handling the needs of the congregation; Responsible for overseeing each service process from beginning to end; and Providing clear and transparent information to the congregation. Thus, this study contributes to enriching the understanding of the factors that influence the satisfaction of Umrah pilgrims and becomes a reference for Umrah travel organizers to develop more effective services that are oriented towards the comfort of the congregation.